(untitled) (Tanzania Medical Journal, 2015)
Background: Tanzania is one of the countries with the highest maternal mortalities in the word and sub Saharan Africa. However, recently there have been reports of a downward trend of this tragedy in Tanzania. Objectives: This study was done to determine the magnitude and the causes of maternal deaths at Dodoma Regional Referral Hospital in Central Tanzania. Methods: A retrospective analysis of all cases of maternal deaths that occurred between January 1st 2007 and December 31st 2011was done at Dodoma Regional Referral Hospital.Results: During this period there were 48776 live birth deliveries and 133 maternal deaths giving the average maternal mortality ratio of 273 per 100,000 live births for the period of five years. During this period the hospital had noted a downward trend of maternal deaths from 356/100,000 in 2007 to 273/100,000 at the end of the review period in 2011. The major causes of deaths were, sepsis (31.5%), obstetric hemorrhages (30.3%) eclampsia (19.1) and obstructed labor (11.2%) in the direct causes? category while in the indirect causes? category the leading causes were anemia and malaria in pregnancy, contributing 38.6% and 29.6% respectively. Generally, most women died from direct causes (66.9%) where, sepsis, hemorrhage and obstructed labor claimed most lives.Conclusion: Though the Hospital has recorded a drop in maternal death, the numbers are still unacceptably high and the major causes of deaths have persistently remained fairly high throughout the study period.